2009
DOI: 10.1111/j.1601-5223.1976.tb01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution in the Ehrlich-Lettré complex of hyperdiploid mouse ascites tumors: Results from seven laboratory strains

Abstract: NIELS~N, K. 1976. Chromosomal evolution in the Ehrlich-Lettre complex of hyperdiploid mouse ascites tumors: Results from seven laboratory strains. -Heredim 84: 77-108. Lund, Sweden,The chromosomes of 7 strains of the hyperdiploid Ehrlich-Lettre mouse ascites tumor (ELD) were analyzed by conventional stainings and by Gand C-bandings. A tendency to slow decrease in chromosome number during a 20-year period was revealed in the 7 strains and in the ELD complex in general. A G-band idiogram of the normal mouse chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…-Among the other markers regularly identified in the present study, some regions showed good resemblance with regions of markers identified earlier (NIELSEN 1976~). Thus, the proximal part (bands qlI-q21) of mar2 of the ELT Bonn was apparently identical with region 1 of mar2 as described in the paper quoted.…”
Section: Chromosome Numbers and Morphologysupporting
confidence: 87%
See 1 more Smart Citation
“…-Among the other markers regularly identified in the present study, some regions showed good resemblance with regions of markers identified earlier (NIELSEN 1976~). Thus, the proximal part (bands qlI-q21) of mar2 of the ELT Bonn was apparently identical with region 1 of mar2 as described in the paper quoted.…”
Section: Chromosome Numbers and Morphologysupporting
confidence: 87%
“…The number of biarmed markers per total chromosome number showed a tremendous increase in comparison with the hyperdiploid Ehrlich-Lettre sublines, in which mostly only one or two biarmed chromosomes per cell are observed (NIELSEN 1976~). The number of the biarmed chromosomes of the present ascites cells varied between 5 and 12 per cell in vivo, and 7 and 12 in vitro.…”
Section: B) Biarrnid Markersmentioning
confidence: 55%